2003
DOI: 10.1053/jhep.2003.50021
|View full text |Cite
|
Sign up to set email alerts
|

A vasopressin receptor antagonist (VPA-985) improves serum sodium concentration in patients with hyponatremia: A multicenter, randomized, placebo-controlled trial

Abstract: for The North American VPA-985 Study Group Hyponatremia in advanced cirrhosis and ascites or congestive heart failure (CHF) is the result of an inappropriate increase in vasopressin secretion, which acts through activation of specific V 2 receptors in the distal renal nephron to increase water reabsorption. This study investigates the efficacy and safety of 3 different doses of the V 2 receptor antagonist, VPA-985, in correcting hyponatremia over a 7-day inpatient study period. Forty-four hospitalized patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
221
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(236 citation statements)
references
References 29 publications
8
221
0
7
Order By: Relevance
“…Finally, it would also be important to study aquaporin-2 excretion in patients with cirrhosis whose serum sodium concentration has been normalized by the administration of V2 receptor antagonists, drugs that increase solute-free water excretion and improve serum sodium levels. 32,33 In conclusion, patients with cirrhosis, particularly those with hyponatremia and hepatorenal syndrome, have decreased urinary aquaporin-2 excretion relative to healthy subjects, which suggests there is down-regulation of aquaporin-2 expression in the kidneys of those with cirrhosis. This may be a compensatory response to the hyponatremia and extracellular fluid volume expansion that patients with cirrhosis have.…”
Section: Aquaporin-1 Protein In Urinementioning
confidence: 94%
“…Finally, it would also be important to study aquaporin-2 excretion in patients with cirrhosis whose serum sodium concentration has been normalized by the administration of V2 receptor antagonists, drugs that increase solute-free water excretion and improve serum sodium levels. 32,33 In conclusion, patients with cirrhosis, particularly those with hyponatremia and hepatorenal syndrome, have decreased urinary aquaporin-2 excretion relative to healthy subjects, which suggests there is down-regulation of aquaporin-2 expression in the kidneys of those with cirrhosis. This may be a compensatory response to the hyponatremia and extracellular fluid volume expansion that patients with cirrhosis have.…”
Section: Aquaporin-1 Protein In Urinementioning
confidence: 94%
“…Yet, an allocation system that incorporates a factor with such wide variability depending on the use of diuretics and fluid status may prevent pretransplant deaths, but also may increase posttransplant mortality, as patients with pretransplant hyponatremia have been shown to have more complications as previously noted. 60,61 Posttransplant Hyponatremia appears to have clinical implications after liver transplant. Patients with hyponatremia before transplant were more likely to develop delirium, renal failure, and infectious complications within the first months after transplant.…”
Section: Clinical Associationsmentioning
confidence: 99%
“…73,74 In addition, other studies such as Okita and associates have suggested a dose-dependent improvement in ascites, lower extremity edema and tolerance to diuretics with tolvaptan, but further research is needed to confirm these findings. 60,61,76,79,80 Conivaptan, approved for only 4 days of intravenous use in the hospital, for euvolemic and hypervolemic hyponatremia, 81 has limited data on its safety and efficacy. [82][83][84] In general, conivaptan was well tolerated with the most common adverse reaction being infusion-site reactions.…”
Section: Clinical Associationsmentioning
confidence: 99%
“…15 From the results of these studies, it has been concluded that lixivaptan is safe and effective at various doses at correcting abnormal renal water handling and hyponatremia in patients who are in a water-retentive state.…”
Section: Lixivaptan (Vpa 985)mentioning
confidence: 99%